Distribution of plastic litter in beach sediments of Silver beach, Cuddalore, during Nivar Cyclone – A first report. (November 2021) - Gandhi, K. Sanjai; Pradhap, D.; Prabaharan, G.; Singh, Satheesh Herbert; Krishnakumar, S.
Abstract: The present study was conducted to assess the distribution of plastic debris in pre- and post-cyclonic beach sediments in Silver beach, Cuddalore, southeast coast of India. The total amount of macroplastic in pre-cyclonic beach sediments was higher than that in the post-cyclonic coastal sediments (pre-cyclonic 16.1%; post-cyclonic 5.4%). The polymer varieties in pre- and post-cyclonic sediments were present in the following descending order: Pre-cyclonic sediments: polyvinyl chloride (79.06%) > polyethylene (13.9%) > nylon (6.9%); post cyclonic sediments: polypropylene (31.4%) > polyethylene (30.5%) > polystyrene (16.0) > nylon (15.5%) > polyvinyl chloride (5.1%). The different varieties of polymers with irregular shapes in the sediments are most probably introduced into the coastal environment by cyclonic floods. Wind and cyclone-induced rainfall were the driving forces for the transportation and deposition of plastic debris. The results of this study will be useful to formulate effective beach litter management policies in an attempt to develop long-term solutions. Highlights: This study documented the distribution of plastic debris in pre and post-cyclonic beach sediments. The sediments were dominated by polystyrene, Polyethylene, polypropylene, nylon, and polyvinyl chloride. The polymers were enriched in post-cyclonic sediments due to the cyclone and cyclone-induced flood.